2021
DOI: 10.18632/aging.202510
|View full text |Cite
|
Sign up to set email alerts
|

GABARAP suppresses EMT and breast cancer progression via the AKT/mTOR signaling pathway

Abstract: Background Recent studies document that γ-aminobutyric acid type A (GABAA) receptor-associated protein (GABARAP) plays an important role in cancer autophagy. However, little is known about its role in tumor invasion, migration and metastasis. Here, the authors investigated the expression and significance of GABARAP in breast cancer. Method: A large group of clinical samples was assessed to detect GABARAP expression and its associations with clinicopathological features and prognosis. Gain-and loss-of-function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The IHC assay was performed as previously described [ 25 ]. Primary antibodies were listed in an Additional file 1 : Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IHC assay was performed as previously described [ 25 ]. Primary antibodies were listed in an Additional file 1 : Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…WB was conducted as previously described [ 25 ]. Briefly, cell lysates were obtained using RIPA lysis buffer (Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies have shown that this is mostly due to their involvement in the selective degradation of several oncogenic proteins, as described for the LC3-mediated degradation of SNAI1 [20,30,51,52]. However, the ATG8 proteins might also be involved in cancer inhibition in a selective-autophagy-independent pathway, via the regulation of several signaling pathways involved in cancer progression [40,53].…”
Section: Discussionmentioning
confidence: 99%
“… 26 But another study result suggested that GABARAP can suppress progression of breast cancer. 27 , 28 GABARAP expresses differently between Glioma and normal brain tissue and has a prognostic value in Glioma patient. 29 GABARAP has a relation with tumorigenesis of melanoma and ablation of GABARAP in mice suppresses tumor growth.…”
Section: Discussionmentioning
confidence: 99%